Do not neglect the indigenous peoples when reporting health and nutrition issues of the socio-economically disadvantaged populations in Malaysia - Khor, Geok Lin; Mohd Shariff, Zalilah (BMC, 2019)
The purpose of this correspondence is to express our disappointment with the coverage of the BMC Public Health supplement: Vol 19 (4) titled “Health and Nutritional Issues Among Low Income Population in Malaysia”, which neglected to include the fundamental health and nutrition issues that are adversely affecting the lives and livelihood of the indigenous peoples. The Supplement comprised 21 papers. Two of these papers included indigenous peoples as study subjects. These two papers addressed peripheral, albeit important health issues, namely visual impairment and quality of life, and not the persistent and rising health concerns impacting this population. We will provide evidence from research and reports to justify our critique that the Supplement missed the opportunity to spotlight on the serious extent of the health and nutritional deprivations of the indigenous peoples of Malaysia. As researchers of the indigenous peoples, we ought to lend our voice to the “silenced minority” by highlighting their plight in the media including scientific journals.